Genetic variation in CHRNA7 and CHRFAM7A is associated with nicotine dependence and response to varenicline treatment. (December 2018) - Cameli, Cinzia; Bacchelli, Elena; Paola, Maria; Giucastro, Giuliano; Cifiello, Stefano; Collo, Ginetta; Cainazzo, Maria; Pini, Luigi; Maestrini, Elena; Zoli, Michele
Abstract The role of nicotinic acetylcholine receptors (nAChR) in nicotine dependence (ND) is well established;CHRNA7, encoding the α7 subunit, has a still uncertain role in ND, although it is implicated in a wide range of neuropsychiatric conditions.CHRFAM7A, a hybrid gene containing a partial duplication ofCHRNA7, is possibly involved in modulating α7 nAChR function. The aim of this study was to investigate the role ofCHRNA7 andCHRFAM7A genetic variants in ND and to test the hypothesis that α7 nAChR variation may modulate the efficacy of varenicline treatment in smoking cessation. We assessedCHRNA7 andCHRFAM7A copy number, CHRFAM7A exon 6 ∆2 bp polymorphism, and sequence variants in theCHRNA7 proximal promoter in an Italian sample of 408 treatment-seeking smokers. We conducted case-control and quantitative association analyses using two smoking measures (cigarettes per day, CPD, and Fagerström Test for Nicotine Dependence, FTND). Next, driven by the hypothesis that varenicline may exert some of its therapeutic effects through activation of α7 nAChRs, we restricted the analysis to a subgroup of 142 smokers who received varenicline treatment. TheCHRNA7 promoter variant rs28531779 showed association with both smoking quantitative measures (FNTDp  = 0.026, β  = 0.89, 95% CI 0.11–1.67; CPDp  = 0.006, β  = 4.82 95% CI 1.42–8.22). Moreover, in the varenicline-treated subgroup we observed association ofCHRFAM7A copy number with 6 months smoking abstinence (p  = 0.035, OR = 3.18, 95% CI = 1.09–9.30). Thus, our study points to a possible role of genetic variation inCHRNA7 andCHRFAM7A in tobacco addiction mechanisms and response to varenicline treatment.